TAF2 condensation in nuclear speckles links basal transcription factor TFIID to RNA splicing factors - Tanja Bhuiyan; Niccolò Arecco; Paulina Karen Mendoza Sanchez; Juhyeong Kim; Carsten Schwan; Sophie Weyrauch; Sheikh Nizamuddin; Andrea Prunotto; Mehmet Tekman; Martin L. Biniossek; Bettina Knapp; Stefanie Koidl; et al. (Cell Reports)
Summary: TFIID is an essential basal transcription factor, crucial for RNA polymerase II (pol II) promoter recognition and transcription initiation. The TFIID complex consists of the TATA binding protein (TBP) and 13 TBP-associated factors (TAFs) that contain intrinsically disordered regions (IDRs) with currently unknown functions. Here, we show that a conserved IDR drives TAF2 to nuclear speckle condensates independently of other TFIID subunits. Quantitative mass spectrometry analyses reveal TAF2 proximity to RNA splicing factors including specific interactions of the TAF2 IDR with SRRM2 in nuclear speckles. Deleting the IDR from TAF2 does not majorly impact global gene expression but results in changes of alternative splicing events. Further, genome-wide binding analyses suggest that the TAF2 IDR impedes TAF2 promoter association by guiding TAF2 to nuclear speckles. This study demonstrates that an IDR within the large multiprotein complex TFIID controls nuclear compartmentalization and thus links distinct molecular processes, namely transcription initiation and RNA splicing.